Upper Respiratory Allergic Symptoms And Effects Of Coal Dust On Pulmonary Function Tests Of Individuals Working In Coal Mines, Near Quetta, Baluchistan, Pakistan - Khan, Zafar Ahmad; Aslam, Muhammad Imran; Ahmad, Muhammad Hashir; Ahmad, Muhammad Tayyab; Ishaq, Hajira; Ahmed, Zahoor (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective This research was carried in order to know hazardous outcomes of coal mine dust on upper respiratory system and their pulmonary function tests. Methodology In this longitudinal cross sectional study, we evaluated upper respiratory allergic symptoms and pulmonary function tests deterioration cause by coal dust exposure in coal mines workers near Quetta, Baluchistan (from October 2018 to March 2019). A total of 336 individuals working in coal mines meeting the preset selection criteria were selected and 41 normal healthy individuals of same age and sex were selected from the general public of the same region who had never been exposed to coal dust/coal mines and served as control group. Results Their pulmonary functions were recorded by (SX MULTI SPIRO, USA) and for the analysis of data SPSS version 18 was employed. The result shown in frequency and percentages, Chi Square test was used and p value of < 0.05 was considered as significant. Conclusion Unprotected exposure to coal dust for longer period of time has bad impact on pulmonary function test and biochemical parameters and is associated with increased frequency of upper respiratory tract allergic symptoms. Key words Quetta, Coal mine, Pulmonary Function Test, Microspheres